Stairwell-Based Meal Delivery During Hospital Elevator Outages in Disasters: A Simulation Feasibility Study - Kamimura, Hiroki; Igarashi, Yutaka; Sakai, Yoshiko; Okada, Ichiro; Koido, Yuichi; Yokobori, Shoji (Universitas Gadjah Mada, 2026)
Introduction: Large-scale disasters can disable hospital elevators, disrupting vertical transport of supplies and meals. Ensuring continued meal provision for inpatients is critical for patient health and hospital continuity. Objective: We simulated a stairway-based “bucket brigade” meal delivery system to quantify the time and staffing required when elevators are out of service, informing hospital disaster business continuity planning. Methods: A relay of 41 staff was stationed from a basement kitchen (B2) to a ward on the 3rd floor. A load of 32 meal trays (one cart) was passed hand-to-hand up the stairs, and return descent times were measured. We extrapolated these results to higher floors (3rd–12th) for a full meal round (64 trays/ward). Results: Delivering 32 trays to 3F took 5 min 56 sec upward and 3 min 49 sec downward. No drops or injuries occurred. Extrapolation indicated 69 min upward and 44 min downward to supply 64 meals to all wards up to 12F, requiring approximately 130 personnel positions. Conclusions: Stairwell delivery is feasible but labor-intensive. Over one hour and a large multidisciplinary team would be needed to deliver meals hospital-wide during elevator outages. Hospitals should incorporate such scenarios into disaster plans to ensure continuity of care.